Morphology and karyology of wild growing Polish representatives of Triticeae (Poaceae) - Mizianty, Marta; Frey, Ludwik (Biodiversity: Research and Conservation, 2006)
Taxonomy (key characters), karyology (chromosome number and genome structure) and some remarks on chorology (general distribution and in Poland) of 9 wild growing species from the tribe Triticeae (Pooideae; Poaceae) belonging to 5 genera (Elymus, Hordelymus, Leymus, Hordeum, Brachypodium) are shortly presented.